The Impact of e-Health for Cancer Patients - Batmetan, John Reimon; Yusuf, Yusnia; Idjie, Elyis Y. C; Ruma, Satin La (JR Education, 2022)
E-Health or Electronic Health is the use of information and communication technology including electronics, telecommunications, computers and informatics to process various types of medical information, to carry out clinical services (diagnose or therapy), administration and education. In E-health the distance factor is not an issue because all activities are carried out through a data connection and in real time. This study discusses the community's analysis of the use of e-Health. This study aims to analyze the impact and influence of convenience and benefit factors on cancer patients using the Technology Acceptance Model (TAM) method. The results of this study indicate that users show positive benefits when using e-health applications. The results of this study also show that e-health has these positive benefits for respondents so they want to continue to use e-health services. Users also get the ease of use which also affects the interest (behavioral intention) in using the E-Health application because the ease of use increases the effectiveness of users